(untitled) (Docentes 2.0 Journal, 2025)
Currently, we find ourselves in a context where Artificial Intelligence (AI) has taken on significant relevance, consolidating itself as a transformative tool in the academic field. Students, through autonomous learning, are responsible for their training as educators. The objective of this research was to analyze the research conducted on the use of AI in higher education institutions, as well as the challenges faced in adapting to technological advancements in the current century. The research was conducted using interpretive paradigm, a systematic method with a qualitative approach, a descriptive narrative design, a bibliographic documentary, and a cross-sectional approach, employing the PRISMA method. Subsequently, publications related to the application of artificial intelligence were selected, identifying opportunities to strengthen professional training and promoting its appropriate, ethical, and responsible use by students and educators. The information search was conducted in recognized academic databases such as Scopus, Eric, Scielo, Web of Science, Dialnet, and Google Scholar. Inclusion and exclusion criteria were applied, allowing for the selection of 13 scientific articles relevant to the research. The results showed that the incorporation of artificial intelligence in higher education has generated multiple benefits for students, faculty, and administrative staff. In conclusion, artificial intelligence has enabled higher education institutions to be better prepared to face current and future challenges, taking advantage of the benefits its implementation offers in academic activities.